Analisis Kepuasan Pelanggan Terhadap Bauran Pemasaran Menggunakan Integrasi Importance Performance Analysis dan Model Kano (Studi Kasus : L’societe Dine and Bar Bandung) - Rizki Wahyuniardi; Asep Syaifulbachri; Rasyid Algaza (Jurnal Rekayasa Sistem Industri, 2018)
The city of Bandung has a variety of culinary places that feature their own characteristics, ranging from luxury culinary venues, traditional uniqueness hangout, to the roadside hangout is available in this city. Amid the rapid development of culinary tourism in the city of Bandung, L'societe Dine and Bar is one restaurant that wrestle in culinary tourism business competition. However, according to sales data, L'societe experienced a decrease in total sales from 2014 to 2016. L'societe requires effective improvement on its marketing mix performance. The study aims to analyze customer satisfaction with L'societe marketing mix. The research was conducted using descriptive statistics method, measuring customer satisfaction index and integration of Importance Performance Analysis and Kano Model.Based on the result of research, there are some attributes of L'societe marketing mix that need to be improved. For price attributes, L'societe should review product prices. This review is conducted through further research on product pricing by analyzing product prices with competitor product price comparison or optimizing production costs. For promotional attributes, L'societe can hold live music on an ongoing basis. In addition to this, it can be proposed packages with attractive discounts to the customer, group or family. This is important to consider because L'societe puts forward a convenient facility to its customers to feel different from its competitors. Keywords: marketing mix, importance performance analysis, integration of importance performance analysis and canoe model, customer satisfaction, Kano model